Impact of socio economic factors to changing energy consumption expenditure of the urban sector (with special reference to arachchikattuwa divisional secretariat division) - Kumari, K.H.M.S.K.; Balasooriya, B.S.K. (university of Jaffna, 2014)
Industrial Revolution causes a dramatic change in energy system, away from locally gathered, traditional fuel such as biomass to commercially traded fossil fuels. New innovations are given high priority to the energy. Then pattern of energy usage is changed day by day. According to the oxford dictionary definition, the power derived from physical or chemical resource to provide light and heat or to work machines is called energy. Energy used in respiratory activities including growth, reproduction and combustion of food and fuel.
Keywords: Economy; Energy system; Expediture